Improved first-pass effect in acute stroke thrombectomy using Solitaire-X compared to Solitaire-FR - Biederko, Ron; Honig, Asaf; Shabad, Ksenia; Zlotnik, Yair; Ben-Arie, Gal; Alguayn, Farouq; Shelef, Ilan; Horev, Anat (Frontiers in Neurology, 2023)
Background: In acute ischemic stroke (AIS), successful endovascular thrombectomy (EVT) of large vessel occlusion (LVO) necessitates the most suited device. Solitaire-X has longer and larger diameter pusher wires than Solitaire-FR. As the role of a larger pusher-wire diameter is uncertain, we aim to compare procedural, clinical, and radiological outcomes for AIS patients undergoing EVT using either type of Solitaire-device. Procedures were performed using the Solumbra technique, which combines a large bore aspiration catheter with a Stentriever. The primary outcome was to compare rates of successful first-pass recanalization (defined as TICI 2b/3 score). The secondary objectives were procedural (rates of successful recanalization), clinical (postprocedural NIHSS and days of hospitalization), and radiological (post-procedural ASPECT score and hemorrhagic transformation) outcome measures. Design: Consecutive AIS patients undergoing EVT for LVO were recruited into a prospective multicenter database at our academic center. We have used Solitaire-FR until October 2020 and Solitaire-X ever since. We retrospectively analyzed our prospective consecutive registry. Included in our analysis are patients undergoing EVT using Solitaire only; patients with tandem lesions or underlying stenosis requiring emergent stenting during the procedure were excluded. The cohort of patients treated with Solitaire-X was compared with a cohort consisting of the most recent consecutive cases undergoing EVT with the Solitaire-FR. Results: A total of 182 (71.9±14, 61% males) AIS patients were included in the analysis with both groups (n=91 each) sharing similar demographic characteristics, premorbid conditions, and stroke characteristics (time from symptom-onset, NIHSS, ASPECTS, occlusion site, and rates of intravenous-tPA treatment). The Solitaire-X group had a higher rate of first-pass recanalization (65.9% vs 50.5%, p=0.049). On 24-hour post-procedural head-CT, The Solitaire-X group had higher ASPECT-scores (6.51±2.9 vs 5.49±3.4, p=0.042) and lower post-procedural average bleeding volumes (0.67±2.1 vs 1.20±3.4 ml, p=0.041). The Solitaire-X group had shorter duration of hospitalization (16.6±13.1 days vs 25.1±23.2, p=0.033). On multivariate analysis, using Solitaire-X was the sole independent predictor of first-pass recanalization (OR 2.17, 95% CI 1.12−4.26, p=0.023). Conclusion: In our study use of the Stentriever-X with larger pusher-wire diameter was associated with a higher likelihood of first pass effect and improved procedural, clinical, and radiological outcomes in AIS patients.